The Christmas basket - Macomber, Debbie (Don Mills, Ont. : MIRA Books, 2002)
Noelle and Thomas, the adult children of two women who have been feuding for years, have been in love since childhood but kept apart by their mothers' bitter battle.
Keywords: Christmas stories